KEBAHAGIAAN PENDUDUK DI PROVINSI JAWA BARAT - Pamungkas, Bambang (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
Happiness is the main goal of every person in his life. Happy or happiness is subjective, so it will be interpreted differently by each individual related to their respective perceptions. The population of West Java in 2017 is happily happy, but it is still at a low level. The high numbers of macroeconomic indicators have still been the main goal in carrying out development. Even though high macroeconomic conditions may not be able to make people happy. Now it is time for local governments to involve their residents more actively from the development planning, so that the development carried out can be more targeted and make the citizens more happy.